Searching for evidence of jet-cloud interaction in radio galaxies: first results for 3C 381 - Reynaldi, María Victoria (2013)
We present results of Gemini spectroscopy and Hubble Space Telescope imaging of the 3C 381 radio galaxy. Possible ionising mechanisms for the Extended Emission-Line Region were studied through state-of-the-art diagnostic analysis employing line-ratios. Photoionisation from the central engine as well as mixed-medium photoionisation models fail in reproducing both the strengths and the behaviour of the highest-excitation lines, such as [Ne v]λ3424, He ii, and [O iii]λ5007, which are measured at very large distances from the AGN. Shock-ionisation models provide a better fit to the observation. Expanding shocks with velocities higher than 500 km s−1 are capable of reaching the observed intensity ratios for lines with different ionisation states and excitation degrees. This model also provide a direct explanation of the mechanical energy input needed to explain the high-velocity line-splitting observed in the velocity field.